188 Challenges in Differentiating Between Obsession and Delusion in Schizophrenic Patients: A Case Report. (April 2020) - Yen, Po Yu; Zaidi, Muhammad; Naqvi, Syed
Abstract: Schizophrenia is a serious, chronic mental illness that manifests a variety of symptoms: hallucinations, delusion of grandiose, disorganized behaviors, and neurocognitive decline after each episode. Among the patients with schizophrenia, obsessive- compulsive symptoms (OCS) or obsessive- compulsive disorder (OCD) are two relatively common comorbidities (25% and 12.5%, respectively). The appearance of these comorbidities complicates patient management: selecting the suitable pharmacological treatment may be challenging as delusion and obsession have similar presentation in this population. We would like to present a case which we suggest that differentiation between obsession and delusion will result in a positive impact on disease management. Patient was a middle- aged male with history of Schizophrenia and status post skin grafting. He presented with delusions, auditory hallucinations and disorganized behavior. During his hospitalization, he spent much portion of a day slapping or hitting his wound. He would not follow staffs' recommendations regarding wound care as he believed that his behavior would lead to diminishing his pain from skin grafting and shorten the recovery time. He was treated with psychotropic medications, anti-depressants aided with medication for pain. Despite adequate pain management, appropriate dosage of anti-depressants and psychotherapy his self- injurious behavior persisted throughout the course of his hospitalization. In this report, we presented the challenges in managing compulsive behavior in a patient with Schizophrenia. To date, OCD and OCS are diagnosed based on clinical presentations, which results in difficulty in patient management especially when the illness is complicated by Schizophrenia. Patient was accessed with Yale- Brown Obsessive- Compulsive Scale on multiple occasions which the results indicated that he had subclinical OCD. However, the validity of the test is questionable as it is a test for severity of OCD; If his compulsive behavior was due to delusion rather than obsession, YBOCS should not be applied since it is limited to the patients with OCD. We propose that there is a necessity of developing a diagnostic intervention that may aid the differentiation between delusion and obsession in Schizophrenic patients. Genetic testing, for example, may be one of the potential diagnostic interventions to utilize clinically: A recent study, "Serotonin system genes and obsessive- compulsive trait dimensions in a population- based, pediatric sample: a genetic association study" by Sinopoli et al, has demonstrated a possible correlation between obsessive- compulsive spectrum disorders and serotonin gene variants. Although genetic testing of OCD is at its early stages and many aspects are yet to be discovered, it is optimistic to believe that potential benefits of the genetic test is tremendous as it will provide physicians a clearer picture in designing a treatment plan for this patient population.